Multi-phase modelling of intergranular hydrogen segregation/trapping for hydrogen embrittlement. (16th November 2015) - Jothi, Sathiskumar; Croft, T.N.; Wright, L.; Turnbull, A.; Brown, S.G.R.
Abstract: Premature failure in polycrystalline materials due to hydrogen absorption affects a wide range of applications, including clean energy systems, hydrogen storage systems and rocket engines. A good understanding of the diffusion and trapping processes within such materials can inform material choices and component design to reduce the likelihood of such failures. Grain boundary segregation of hydrogen can often lead to intergranular hydrogen embrittlement (IHE). In order to understand the effects of hydrogen on intergranular and transgranular fracture in polycrystalline material it is important to first understand hydrogen diffusion and trapping in the general context of grain boundary segregation engineering (GBSE). Hydrogen diffusion is affected by local microstructural features including intergranular second phase precipitates, grain boundary (GB) thicknesses and geometrically necessary dislocation (GND) density. A multi-scale multi-phase model is presented here that has been developed to study GBSE with respect to hydrogen diffusion and IHE. The results of various multi-scale GBSE models with and without traps (including the effects of microstructure, intergranular precipitate phases and GB thickness) are compared and discussed, and the effects of microstructural parameters such as hydrogen segregation factor and GND trapping density on hydrogen diffusion are investigated. Graphical abstract: Highlights: Several multi-scale FE models have been developed using MATLAB & PYTHON scripting. User element subroutine (UEL) has been developed for trap model using FORTRAN code. Monte Carlo (MC) model has also been developed for realistic GB misorientation. Calculated the geometric necessary dislocation (GND) trap density variations. Investigated the effects of GB segregation of hydrogen on hydrogen embrittlement.